2020
DOI: 10.1111/pan.13811
|View full text |Cite
|
Sign up to set email alerts
|

Reducing postoperative pain in children undergoing strabismus surgery: From bundle implementation to clinical decision support tools

Abstract: Background: Postoperative pain is a significant cause of morbidity in pediatric anesthesia, which can result in delayed discharge and unplanned hospital admission.Children undergoing strabismus surgery are known to be a particularly high-risk group for postoperative pain.Aim: The aim of this project was to reduce the incidence of moderate to severe postoperative pain by 25% over a period of 12 months in children undergoing strabismus surgery. Methods:This was a multidisciplinary quality improvement project usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…This study is the first to be performed in Colombia with the aim of determining the incidence of postoperative vomiting in the pediatric population aged 3 to 12 years. The incidence of POV was 18.95%, very similar to the 18% incidence reported by Ali et al in a retrospective study of 1079 children (16). These values are within the range described in the literature of 7.3% (2) to 82% (3).…”
Section: Discussionsupporting
confidence: 88%
“…This study is the first to be performed in Colombia with the aim of determining the incidence of postoperative vomiting in the pediatric population aged 3 to 12 years. The incidence of POV was 18.95%, very similar to the 18% incidence reported by Ali et al in a retrospective study of 1079 children (16). These values are within the range described in the literature of 7.3% (2) to 82% (3).…”
Section: Discussionsupporting
confidence: 88%
“…Pain after strabismus surgery can cause emotional distress to both patients and parents and can result in poor family satisfaction and delayed discharge from hospital. The mean monthly incidence of moderate to severe postoperative pain following pediatric strabismus surgery was 47.3% as reported by Ali et al 11 An earlier study reported the incidence of clinically significant pain to be as high as 65%. 12 In the present study, muscle fenestration technique was more significantly painful at the first day following the operation.…”
Section: Discussionmentioning
confidence: 57%
“…A total of 45 separate CDSSs were reported in the 42 articles included as shown in Table 2 . The most commonly reported CDSSs were electronic prescribing or order sets (12/42, 29%) [ 65 , 69 , 70 , 75 , 76 , 79 - 81 , 83 , 88 , 94 , 98 ], followed by checklists, forms, or clinical guidelines (11/42, 26%) [ 63 , 66 , 73 , 82 , 89 , 92 , 93 , 95 , 102 , 104 ] and electronic alerts or reminders (9/42, 21%) [ 67 , 68 , 77 , 78 , 84 , 86 , 91 , 100 , 101 ]. Commonly, CDSSs were implemented in pharmacy or prescription services (17/42, 41%).…”
Section: Resultsmentioning
confidence: 99%